ANALISIS DAMPAK DAYA TARIK WISATA MENGGUNAKAN PARTIAL LEAST SQUARE STRUCTURAL EQUATION MODELING (PLS-SEM) - Auda Nuril Zazilah; Sri Hidayati; Fajar Isnaeni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2023)
This study aims to analyze the impact of the tourist attraction of Oling River Food Banyuwangi on the social, economic and environmental fields. By using Partial Least Square – Structural Equation Modeling (PLS-SEM) which is based on the Ordinary Least Square (OLS) method, it is found that tourist attraction to the economy has a significant positive effect with a path coefficient of 0.75, a positive effect on the environment and a significant effect with a path coefficient of 0.67 , as well as a positive and significant social effect with a path coefficient of 0.832. The tourist attraction variable is significantly influenced by the environment, social, economy by 69.2%. This means that if the tourist attraction of oling river food is getting better and growing, the community's economy will increase, the environment will be better maintained and the social relations of the surrounding community will get better.